Body weight and the prevalence of chronic diseases. Issue 1 (March 1988) - Negri, E; Pagano, R; Decarli, A; La Vecchia, C
Abstract : The relation between body mass index and prevalence of 17 chronic diseases or groups of diseases was analysed using data from the 1983 Italian National Health Survey, based on a sample of 72, 284 individuals aged 15 or over randomly selected within strata of geographical area, size of place of residence and of household in order to be representative of the whole Italian population. The prevalence of diabetes was directly and strongly related to body weight (age-adjusted relative risk estimates being 1.5 for overweight and 2.7 for obese men compared with normal weight individuals; 1.6 and 2.4 for overweight and obese women). Other conditions directly related to self-reported measures of body weight were hypertension (relative risk = 1.7 for obese men and 1.9 for women), myocardial infarction (relative risk = 1.5 for obese men, 1.6 for women), other heart diseases (relative risk = 1.7 for obese men, 1.5 for women), haemorrhoids or varices (relative risk = 1.2 for obese men, 1.5 for women), cholelithiasis (relative risk = 1.2 for obese men, 1.4 for women), urolithiasis and arthritis. Chronic respiratory disorders showed a U-shaped relation to measures of body weight, since their prevalence was elevated in both under- and over-weight individuals. Anaemias and gastroduodenal ulcer showed an inverse relation to body weight, whereas no association was apparent with allergy, liver cirrhosis, and psychiatric or neurological disorders. Allowance for the two major identified covariates (education and smoking) failed to explain the observed variations between measures of body weight and disease, while separate inspection of various strata of age indicated that for most diseases the elevated risks of obesity were higher in younger and decrease steadily with advancing age. Thus, the results of this national survey indicate that overweight has a widespread and substantial impact not only on mortality but also on morbidity from different chronic conditions.